(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Nanotechnology is not only a simple continuation of miniaturization from micron meter scale down to nanometer scale. Because of their small size which gives large surface areas, they can lead to unexpected or dramatically differing properties than the bulk. Different sized nano materials exhibit different properties. For example bulk gold has golden color but the gold nano particle having diameters of >1nm and 3-30 nm has orange and red colors. They are useful candidates for many applications like solar cells, batteries, computer chips, cosmetics, drug delivery, optoelectronic devices, catalysis, display devices, photo and electroluminescent devices, spintronics, sensors etc. leading them to enter the world market in a big way. Although many countries are majorly investing in this field of nanotechnology.Natural inorganic nanomaterials occur through crystal growth in the diverse chemical conditions of the earth’s crust. Fullerenes, carbon nanotubes are some of the examples of synthetic organic nanomaterials. Inorganic nanomaterials are based on other elements, such as silicon. Solids and molecules have been studied and understood quite well, however nanomaterials exhibits properties that are entirely different from either of the two. If the physical size of the material is reduced below the nanometer length scale, it’s all properties like mechanical strength, thermal, optical, magnetic, conducting etc. change and become sensitive to its size and shape.